PAK1 Mediates Bone Marrow Stromal Cell-Induced Drug Resistance in Acute Myeloid Leukemia via ERK1/2 Signaling Pathway - Li, Banban; Jia, Ruinan; Li, Wei; Zhou, Ying; Guo, Dongmei; Teng, Qingliang; Du, Shenghong; Li, Mingying; Li, Wěi; Sun, Tao; Ma, Daoxin; Ji, Min; et al. (Frontiers in Cell and Developmental Biology, 2021)
Background: Chemoresistance is emerging as a major barrier to successful treatment in acute myeloid leukemia (AML), and bone marrow stromal cells (BMSCs) protect leukemia cells from chemotherapy eventually leading to recurrence. This study was designed to investigate the role of p21-activated kinase 1 (PAK1) in AML progression and chemosensitivity, highlighting the mechanism of stroma-mediated chemoresistance. Methods: The GEPIA and TCGA datasets were used to analyze the relationship between PAK1 mRNA expression and various clinical parameters of AML patients. Cell proliferation and apoptosis were examined to evaluate the role of PAK1 on chemosensitivity in AML by silencing PAK1 with shRNA or small molecular inhibitor. Human bone marrow stromal cell (HS-5) was utilized to mimic the leukemia bone marrow microenvironment (BMM) in vitro, and co-culture model was established to investigate the role of PAK1 in BMSC-mediated drug resistance. Results: PAK1 high expression was shown to be associated with shorter overall survival in AML patients. The silence of PAK1 could repress cell proliferation, promote apoptosis, and enhance the sensitivity of AML cells to chemotherapeutic agents. More importantly, BMSCs induced PAK1 up-regulation in AML cells, subsequently activating the ERK1/2 signaling pathway. The effect of BMSC-mediated apoptotic-resistance could be partly reversed by knock down of PAK1. Conclusion: PAK1 is a potential prognostic predictor for AML patients. PAK1 may play a pivotal role in mediating BMM-induced drug resistance, representing a novel therapeutic target in AML.